2007
DOI: 10.1016/j.jbusres.2006.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturer perceptions of the consequences of task and emotional conflict within domestic channels of distribution

Abstract: This study examines manufacturer' perceptions of task and emotional conflict in domestic channels of distribution. Both are expected to depend on three antecedents (centralization, esprit de corps, and communication barriers) and to affect performance relative to competitors and manufacturer's satisfaction directly and indirectly through strategy quality. The results support a positive link between task and emotional conflict and the deleterious effect of emotional conflict on satisfaction and performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 27 publications
0
40
0
Order By: Relevance
“…Rose, Shoham, Neill, and Ruvio (2007), in contrast, found that task conflict does not improve performance and strategy quality, and that task conflict can spill over into emotional conflict, which in turn lowers strategy quality. However, conflict in marketing channels, as a reviewer notes, can either disrupt marketing performance or be a learning experience.…”
Section: Theoretical Implicationsmentioning
confidence: 87%
See 1 more Smart Citation
“…Rose, Shoham, Neill, and Ruvio (2007), in contrast, found that task conflict does not improve performance and strategy quality, and that task conflict can spill over into emotional conflict, which in turn lowers strategy quality. However, conflict in marketing channels, as a reviewer notes, can either disrupt marketing performance or be a learning experience.…”
Section: Theoretical Implicationsmentioning
confidence: 87%
“…The focus of this research is on the learning experience. Rose et al (2007) did not consider that conflict, by itself, is potentially a positive learning and knowledge management process in marketing channel relationships. This study differs, and provides insights into how CCL enhances joint marketing strategy quality from a conflict-learning perspective in marketing channel relationships.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Emotional conflict is often viewed as harmful because it tends to be personal, denigrates a relationship and focuses on non-task-related disagreement between parties (Rose, Shoham, Neill, & Ruvio, 2007). It is particularly damaging to collaboration within relationships (Deutsch, 1977), resulting in dispute and lack of coordination between parties within the relationship (Teece, 2000).…”
Section: Conflict Managementmentioning
confidence: 99%
“…Task is considered as functional based on a diversity of viewpoints and results in a more thorough discussion of multiple factors, thus contributing to relationship building by resolving logistical or tactical issues (Rose & Shoham, 2004). Some studies find task conflict to have a constructive impact on business performance (Rose et al, 2007), but other studies find task conflict to negatively influence performance (Chang & Gotcher, 2010; because task conflict can D.A. Yen et al Industrial Marketing Management 66 (2017) 103-114 block or destroy value co-creation (Mele, 2011;Möller & Törrönen, 2003), impacting the economic performance of the relationship (Johnsen & Ford, 2006;Lee & Johnsen, 2012).…”
Section: Conflict Managementmentioning
confidence: 99%
“…As the companies feel that their voice and contribution to directly address points of concern at a rather early stage is valued, their motivation is increased, helping minimize the risk that dissent manifests into conflicts [22,69]. Third, acting jointly in PM strengthens interpersonal relations [22,73] that leads to a benevolent atmosphere and helps establishing pride for being a member of the alliance [74,75]. Strong interpersonal ties and pride in the alliance will facilitate internal cohesion (i.e., an esprit de corps), a sense of belonging together, and maintaining their belief into the alliance even when exposed to internal or external challenges.…”
Section: Symmetrical Power Alliancesmentioning
confidence: 99%